2013
DOI: 10.5267/j.msl.2013.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Strategic planning and performance measurement using balanced scorecard: A case study of Iran Kaolin and Barite company

Abstract: This paper presents an empirical investigation to measure the performance of a mining firm in province of Semnan, Iran based on balanced scorecard (BSC). The proposed study investigates the present status of the case study in terms of four BSC perspectives including internal process, learning and growth, customer and financial figures. The firm uses BSC for one year and after that, we compared the performance of the firm prior and after BSC implementation. The preliminary results indicate that the firm was abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Sofiyabadi et al (2012) presented an integrated balanced score card combined with DEMATEL technique to prioritize different alternatives for supply chain implementation. Danaei and Omidifard (2013) performed strategic planning and performance measurement using balanced scorecard (BSC) (Kaplan & Norton, 1992, 1996, 2004 for the same case study. The results of their survey indicated that the firm was able to make a 30% improvement on its performance after one-year implementation of BSC.…”
Section: Discussionmentioning
confidence: 99%
“…Sofiyabadi et al (2012) presented an integrated balanced score card combined with DEMATEL technique to prioritize different alternatives for supply chain implementation. Danaei and Omidifard (2013) performed strategic planning and performance measurement using balanced scorecard (BSC) (Kaplan & Norton, 1992, 1996, 2004 for the same case study. The results of their survey indicated that the firm was able to make a 30% improvement on its performance after one-year implementation of BSC.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2012) presented an integrated hierarchical BSC with fuzzy linguistic for evaluating operating room performance in hospitals. Danaei and Omidifard (2013) presented a strategic planning and performance measurement using BSC for a case study of Iran Kaolin and Barite company.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that profit margin was the most important item followed by profit capability and brand name while productivity and sales force performance were the least important items. Dabaei and Omidifard (2013) presented a study to measure the performance of a mining firm in province of Semnan, Iran based on BSC. They investigated the present status of the case study in terms of four BSC perspectives including internal process, learning and growth, customer and financial figures.…”
Section: Introductionmentioning
confidence: 99%